Peran Brand Love dalam Memoderasi Pengaruh Brand Satisfaction dan Brand Trust pada WOM - Putri Tanti Ayuningsih; Rini Kuswati (Faculty of Economics and Business University of Lampung, 2023)
This study aims to analyze the role of brand love in moderatingeffect of brand satisfaction and brand trust on word of mouth (WOM). This study uses a sample size of 200 respondents who know or have purchased Make Over products. Sampling technique using non-probability sampling by method purposive sampling. Data analysis using SMARTPLS by using the outer model and inner model. The research findings show that brand satisfaction has a significant positive effect on WOM, brand trust has a significant positive effect on WOM. Meanwhile brand love significant positive effect on WOM. The moderation effect test shows that brand love is shown to moderate influence brand satisfaction on WOM. Temporary brand love not shown to moderate influence brand trust on WOM. This finding explains that the higher the love for a brand, the stronger the influence of brand satisfaction on WOM in Indonesian millennial youth.